MODAL SOSIAL DAN PELESTARIAN LINGKUNGAN MASYARAKAT BANTARAN SUNGAI JANGKOK KELURAHAN DASAN AGUNG KOTA MATARAM - Kutbi Rais, Ahmad; Ibrahim; Nurhayati, Nurhayati; Sukuryadi, Sukuryadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
Based on the 2022 Indonesian Environmental Status document (SLHI 2022), 59.05% of rivers in Indonesia have the status of heavily polluted, 26.61% are moderately polluted and only 8.87% are lightly polluted which meet good quality status. Based on the results of observations by researchers in 2024 carried out in the field, quite a few riverbank residents in Dasan Agung sub-district have the habit of throwing rubbish on riverbanks, so this has a negative impact on the sustainability of the Jangkok River Basin. This is certainly an illustration of the weakness of the social capital system. local community. The aim of this research is to determine social capital strategies for environmental preservation and determine the best social capital for environmental preservation along the Jangkok River. This type of research is qualitative. and Quantitative. This research method uses questionnaires or questionnaires as well as interview observations to collect data, then the data is analyzed using linear regression data processing techniques using the SPSS program. The results of the research show that the effect of social capital on environmental conservation is 93%. This shows that social capital has a significant effect on environmental preservation in the communities along the Jangkuk River, Dasan Agung sub-district, Mataram city. The highest aspect of social capital is the network aspect at 55.73%, the trust aspect at 28.09 or 30.21%, while norms contribute 9.14 or 9.84%. The conclusion of this research is that social capital has a significant effect on environmental preservation on the banks of the Jangkok River, Dasan Agung Village, Mataram City, with the network aspect being the best option for preserving the environment on the banks of the Jangkok River, Dasan Agung Village.